Mothering Children in Africa: Interrogating single parenthood in African literature - Olayiwola,Abiodun (2013)
The issue of motherhood in African womens writings has transcended the façade of binary oppositions created by radical Western feminists who pitch women against men in their campaign for gender equality or, worse still, belittle or show disdain for the men-folk. The approach of African women writers takes issue with the collapse of social inequalities and its potentially disastrous implications. This essay examines the representations of African women in their struggle against the divisive impact of single parenthood in the present economic crisis and their lack of power to cope with the challenges that this crisis poses. By means of a critical and evaluative textual analysis, the essay looks at how contemporary fictional writing succeeds in representing this diffuse social reality.